Integrating Phenotypic and Gene Expression Linkage Mapping to Dissect Rust Resistance in Chickling Pea - Santos, Carmen; Martins, Davide Coelho; González-Bernal, María José; Rubiales, Diego; Vaz Patto, Maria Carlota (Frontiers in Plant Science, 2022)
Rusts are among the most important foliar biotrophic fungal diseases in legumes. Lathyrus cicera crop can be severely damaged by Uromyces pisi, to which partial resistance has been identified. Nevertheless, the underlying genetic basis and molecular mechanisms of this resistance are poorly understood in L. cicera. To prioritize the causative variants controlling partial resistance to rust in L. cicera, a recombinant inbred line (RIL) population, segregating for response to this pathogen, was used to combine detection of related phenotypic- and expression- quantitative trait loci (pQTLs and eQTLs, respectively). RILs’ U. pisi disease severity was recorded in three independent screenings at seedling (growth chamber) and in one season exploratory screening at adult plant stage (semi-controlled field conditions). A continuous disease severity range was observed in both conditions and used for pQTL mapping. Different pQTLs were identified under growth chamber and semi-controlled field conditions, indicating a distinct genetic basis depending on plant developmental stage and/or environment. Additionally, the expression of nine genes related to U. pisi resistance in L. cicera, was quantified for each RIL individual and used for eQTL mapping. One cis-eQTL and one trans-eQTL were identified controlling the expression variation of one gene related to rust resistance- a member of glycosyl hydrolase family 17. Integrating phenotyping, gene expression and linkage mapping allowed prioritizing four candidate genes relevant for disease resistance precision breeding involved in adaptation to biotic stress, cellular and organelle homeostasis and proteins directly involved in plant defense.